Why Can't We Accurately Predict Others' Decisions? Prediction Discrepancy in Risky Decision-Making - Sun, Qingzhou; Zhang, Huanren; Zhang, Jing; Zhang, Xiaoning (Frontiers in Psychology, 2018)
Individuals often fail to accurately predict others’ decisions in a risky environment. In this paper, we investigate the characteristics and causes of this prediction discrepancy. Participants completed a risky decision-making task mixed with different domains (gain vs. loss) and probabilities (small vs. large), with some participants making decisions for themselves (the actor) and the others predicting the actors’ decisions (the predictor). The results demonstrated a prediction discrepancy: predictions were more risk-averse than the actual decisions over small-probability gains and more risk-seeking over large-probability gains, while these patterns were reversed in the loss domain. Reported and predicted levels of emotional stimulation revealed a pattern that is consistent with the notion of risk-as-feelings and empathy gaps. Mediation analysis provided strong evidence that such prediction discrepancy is driven mainly by the predictor’s underestimate of the intensity (not the impact) of the actor’s emotional state.